Menganalisis Struktur Batin Puisi “Bukit Biru, Bukit Kelu” Karya Taufik Ismail - Jihan suni; Rismayanti Rismayanti (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
Poetry is an expression of a writer's heart from his life experiences expressed in the form of beautiful text that is imaginative and has deep meaning. Required in-depth analysis to reveal the meaning contained in it. This researchaims to reveal the inner structure contained in the poem Bukit Biru, BukitKelu by Taufik Ismail. The method used uses content structure analysis which includes theme, feeling, tone and atmosphere as well as message. Results obtained shows that the theme of the poem is in a calm atmosphere, but must be optimistic, feeling.I conveyed the lyrics in the form of an optimistic spirit, the tone and atmosphere showed patriotic and firm, as well as a mandate that upholds optimism. This research is very.It is important to see the meaning contained in the poem Bukit Biru, Bukit Kelu by Taufik Ismail so that the meaning can be conveyed to the audience.